CRITERIA FOR SELECTION OF THE REINSURANCE COVERAGE FOR EXCESS OF LOSS TREATY - V. Veretnov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Optimal reinsurance coverage, selected by the cedent, influenced by a number of internal, external, objective and subjective factors. Their accounting or ignoring depends on the individual conditions of the insurer, knowledge of the specific risk profiles of professional experience and decision-makers about the forms and methods of reinsurance coverage. Justified the selection criteria of reinsurance protection for the treaty excess of loss. Using these criteria makes it possible not only to optimize the reinsurance protection, but also to ensure a balance of interests in the long-term relationship of the cedent company and the reinsurer. The article also provides examples of how classes of insurance is advisable to use the obligatory contract portfolio sexcess of loss.